Determination of histopathologic risk factors for postoperative atrial fibrillation in cardiac surgery - ARSAN, SİNAN (ELSEVIER SCIENCE INC, 2005)
Background. Postoperative atrial fibrillation is one of the most common complications after coronary artery bypass grafting. This study aimed to identify preoperative histopathologic risk factors for the development of postoperative atrial fibrillation. Methods. One hundred elective coronary artery bypass grafting patients were enrolled into the study. Right atrial tissue from all patients was sampled before cardiopulmonary bypass. Patients were monitored for the occurrence of the postoperative atrial fibrillation. Right atrial tissue samples from the atrial fibrillation group were compared with samples belonging to the patients who remained in sinus rhythm postoperatively. Evaluation for atrial histopathology and myocyte apoptosis included light microscopic and immunohistochemical studies. Results. Fourteen of 100 patients (14%) developed postoperative atrial fibrillation. On univariate analysis, the only predictor for the development of postoperative atrial fibrillation was chronic obstructive pulmonary disease (p = 0.014). Histologically, larger sized myolytic vacuoles were more common in patients who developed postoperative atrial fibrillation (p = 0.001). The percentage of apoptotic myocytes in each specimen was significantly higher in patients with atrial fibrillation (p = 0.000). Most of the specimens with positive apoptotic staining were also severely myolytic in patients with postoperative atrial fibrillation. Conclusions. Our results suggest that degree of myolysis and increased apoptotic pattern in right atrial myocardium are significant predictors for the development of postoperative atrial fibrillation. The improvement of preoperative metabolic status of the myocardial cells may reduce the incidence of this common complication. (c) 2005 by The Society of Thoracic Surgeons.
Keywords: CELL-DEATH; HEART; APOPTOSIS; PREDICTORS; OPERATIONS; PATHOLOGY; FIBROSIS; OUTCOMES